From Transvestite Text to Militant Camp: A Comparison Between A. Corteau’s The Book Of Katerina and K. Tahtsis’ The Third Wedding Wreath (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2024)
The article provides a close reading of the novel Το βιβλίο της Κατερίνας [The Book of Katerina] by Auguste Corteau, highlighting its connections and divergences from Το τρίτο Στεφάνι [The Third Wedding Wreath] by Kostas Taktsis. It explores issues of social gender, family, and autobiography through the lens of camp discourse. From a theoretical perspective, the analysis builds on Fabio Cleto’s considerations of queer readings of camp discourse.